Magnitude e fatores associados ao envolvimento espírita, transtornos mentais comuns e ideação suicida: um estudo seccional no Ceará - Sales, Tiago Medeiros (2023)
In the 19th century, Kardec originated a scientific, philosophical and religious movement: spiritism, which attracts individuals in psychic suffering regardless of religious belief. Currently, suicidal ideation and Common Mental Disorders (CMDs) are very prevalent, motivating people to get involved with spiritism, but studies are still scarce. This research aimed to measure the magnitude and factors associated with spiritist involvement in relation to suicidal ideation, stress, anxiety and depression. It was a methodological and cross-sectional study, carried out with people with spiritist involvement in the state of Ceará, between the years 2021 and 2022. The first step was the creation and validation of the Spiritist Involvement Form (SIF), composed of sociodemographic profile, psychic state, psychic assistance and Level of Spiritist Involvement (LSI). Next, digital collection was performed using the Snowball technique, using SurveyMonkey®, data from the SIF, the Depression, Anxiety and Stress Scale (DASS-21) and the Multiattitudinal Suicide Tendency Scale (EMTAS), with subsequent descriptive, bivariate (p < 0.05), multivariate (p < 0.30) and multinomial (p < 0.05) analysis using SPSS 20.0®. The sample consisted of 848 people. Severe stress and anxiety were more associated with “low” and “very low” LSI, before and during the pandemic. Severe depression had a lower prevalence for “high/very high” LSI, before and during the pandemic (2.7% and 5.0%, respectively), in relation to “low” LSI (7.7% and 9.5%, respectively) and “very low” LSI (10.7% and 9.9%, respectively). Severe suicidal ideation was less prevalent for “high/very high” LSI, before and during the pandemic (9.8% and 10.1%, respectively), when compared to “low” LSI (21.4% and 20. 1%, respectively) and “very low” LSI (22.2% and 26.5%, respectively). The factors associated with severe suicidal ideation were: being single (OR = 4.05; IC 1.89 - 8.69), being unemployed (OR = 2.93; IC 1.45 - 5.92), having self-perception of emotional health as regular, poor/terrible (OR = 4.84; IC 2.55 - 9.17), having been in psychotherapy before COVID-19 (OR = 2.57; IC 1.40 - 4.71) and identify with spiritism (OR = 2.13; IC 1.00 - 4.52). Mental suffering was the only reason for seeking spiritism, with association with severe suicidal ideation (OR = 2.11; IC 1.11 – 3.99). “Regular/high/very high” pre-pandemic LSI was protective for severe suicidal ideation during the pandemic (OR = 0.38; IC 0.16 - 0.90). The data reinforced that spiritualism attracts people in psychological distress and that high NEE is less associated with severe TMCs and suicidal ideation than low LSI.